The experiences and support needs of family/supporting adults who accompany someone to the Emergency Department with self-harm, suicide-related ideation and suicide attempt. - Doyle, Louise; Keogh, Brian; Reilly, Roisin; Morrissey, Jean (Trinity College Dublin, 2025)
The Emergency Department (ED) represents an important setting for intervention around self-harm and suicide prevention (Ceniti, Heinecke & McInerney, 2020), particularly as it is often the first entry point to the health system and a gateway to accessing follow-on services (Egan et al., 2012). In Ireland in 2023, there were 12,792 presentations to Emergency Departments for treatment of self-harm (Joyce et al., 2025). On discharge from the ED, family members and others who accompany the person to the ED and/or support the person at home often bear the heaviest responsibility for keeping their family member safe (Juel et al., 2021). Recognising their importance, the National Clinical Programme for Self-Harm and Suicide-Related Ideation (NCPSHI) (Health Service Executive, 2022) identifies that the experiences of families and carers can be crucial in trying to support those who present with self-harm. Despite this, these experiences have not been elicited systematically and there are few published studies in Ireland identifying the experiences and support requirements of families and supporting adults. This study therefore aims to elicit experiences of family members and other supporting adults to identify how they can be better equipped to support the person presenting to the ED with self-harm, suicide-related ideation and suicide attempt to improve outcomes for all. This study builds on an existing collaboration between the research team at Trinity College Dublin and the suicide prevention charity 3ts. In 2020, our study ‘Accessing Help for Self-Harm and Suicidal Behaviour in the Emergency Department: The Experiences of Service Users’ was published, funded by the 3ts (Doyle et al., 2020). Findings from this study demonstrated the importance of family support of the person who presents with self-harm/suicidal ideation both in the ED, and after discharge. However, it also identified, from the perspective of the service-user, that families were often left with the ‘burden of observation’ and ‘surveillance’ following self-harm with no information about how best to help, leaving them feeling insecure and uncertain about their own ability to cope or prevent future incidents. The Irish Mental Health Policy ‘Sharing the Vision’ (Department of Health, 2020) also recognises the importance of family members as a supportive resource to those experiencing mental health difficulties. Family members or other accompanying adults who support a person presenting to the ED with self-harm or suicidal ideation can provide crucial collateral to clinicians (Collom et al., 2019) and support on discharge to the person. Their presence with the person in the ED can improve engagement with services by impacting on their decision to stay for assessment, treatment and onward referral (Doyle et al., 2020). One of five programme objectives of the revised Model of Care of the NCPSHI is to optimise the experience of families and carers in supporting those who present to the ED with self-harm and suicide-related ideation (HSE, 2022). By eliciting the experiences and importantly the information and support needs of people who accompany someone to the ED and/or who support them at home, findings from this study will provide the basis from which to improve support provided to family members and other supporting adults contributing ultimately to better outcomes for the service user and their family/supporting adult.
PUBLISHED
Keywords: Inclusive Society; Self-harm; Suicide and Suicidal Behaviour; emergency department